How do I do these 2?
a) x/(x^2+x-6)
Tried quotient rule it gave me -x^2 - 6/(x^2+x+6)^2, I don't think it's right
b) 4/(x^2+4x+4)
Tried substitution (because theres another similar question between these two on the paper and that was the way to go for it) Don't think my answers worth mentioning
OK, I was able to get your answer for b) but by using:
u.v-(integral of)(v.du/dx)
u=4
du/dx=0 (That gets rid of the integral part)
v=-(x+2)^-1
dv/dx= (x+2)^-2
so: 4.-(x+2)^-1
It would be nicee if you could show me how to do it your way (using substitution) aswel